Silicon-containing adhesive with high adhesive strength and preparation method thereof

By adopting a collaborative combination method of modified inorganic silicone adhesive and silicone adhesive, the hollow core-shell structure, hindered phenol structure and crosslinking agent, the problem of existing silicone adhesives being difficult to have both anti-aging, heat resistance and flexibility is solved, and the preparation of high-adhesion silicone adhesive is achieved, which is suitable for the application of film materials and special-shaped equipment.

CN119592234APending Publication Date: 2025-03-11YELLOW RIVER YUAN CO LTD +4
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411931510.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

While existing silicone adhesives have excellent anti-aging properties and heat resistance, they are difficult to have good flexibility, light transmittance, transmittance and low refractive index, especially cannot meet the needs of folding equipment and special-shaped film materials.

Method used

By preparing a high-adhesive silicon-containing adhesive, the composite collaborative method of modified inorganic silicone adhesive and silicone adhesive is adopted, and the hollow core-shell structure, hindered phenol structure and crosslinking agent are used to improve the light transmittance, anti-aging yellowing properties, temperature resistance and impact strength of the adhesive.

Benefits of technology

It realizes that the adhesive has good flexibility, light transmittance, transmittance and low refractive index while maintaining high adhesion and anti-aging properties. It is suitable for the preparation of film materials and is especially suitable for folding equipment and special shape applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005210436560000021
    Figure BDA0005210436560000021
  • Figure BDA0005210436560000033
    Figure BDA0005210436560000033
  • Figure BDA0005210436560000081
    Figure BDA0005210436560000081
Patent Text Reader

Abstract

The invention relates to the technical field of organic silicon-based adhesives, in particular to a high-bonding-force silicon-containing adhesive and a preparation method thereof.The high-bonding-force silicon-containing adhesive comprises a modified inorganic silicon adhesive and an organic silicon adhesive according to the mass ratio of 1: (0.8-1.5); the modified inorganic silicon adhesive is composed of a hollow core layer and a shell layer. The adhesive provided by the invention has binding power, good flexibility, aging and yellowing resistance, light transmittance and transmittance, and is more suitable for preparation of membrane materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of silicone-based adhesives, and in particular to a high-adhesion silicone-containing adhesive and a preparation method thereof. Background Art

[0002] Adhesives can be found everywhere in our daily lives. For example, the screen film layers of electronic devices such as mobile phones, tablets or TVs require adhesives in the preparation process. Traditional adhesives are mainly acrylic and polyurethane based. However, these traditional adhesives have poor anti-aging and temperature resistance, and will turn yellow after long-term use, which is particularly evident in car headlight housings. Therefore, a large number of researchers have begun to study silicone adhesives.

[0003] The development of silicone adhesives is closely related to the progress of silicone chemistry as a whole. Initially, silicone adhesives were mainly used to seal and protect electronic components. Due to their excellent electrical insulation properties and temperature resistance, they were soon used in the electronics and electrical industries. With the development of materials science, silicone adhesives began to expand into more fields. In the 1950s, silicone adhesives began to be used in the construction industry for bonding and sealing glass and metal. In the 1960s, with the rise of aerospace technology, silicone adhesives were used in the manufacture of spacecraft due to their stability in extreme environments.

[0004] However, with the continuous development of science and technology, higher requirements are put forward for the performance of organic silicon adhesives. For example, CN110819299B discloses that "thermal conductive organic silicon adhesive" can improve the bonding strength and gas barrier properties to LED chips while maintaining good thermal conductivity by adding specific branched organic polysiloxanes with alkenyl, cycloalkyl epoxy and dicycloalkyl siloxane chain segments. For another example, CN113286863A discloses "organic silicon adhesive composition and its use" by combining polyorganosiloxane with carbon-carbon unsaturated double bonds added to the end of the molecular chain, linear polyorganosiloxane with terminal silicon-bonded hydrogen atoms, polyorganosiloxane resin, and polyorganosiloxane containing at least one aliphatic unsaturated carbon-carbon double bond in the chain segment, and has excellent mechanical strength, elongation and bonding force.

[0005] However, in some special materials, the adhesive is not only required to have bonding strength, but also to have good flexibility, anti-aging and yellowing ability, light transmittance, transmittance and low refractive index. Summary of the invention

[0006] The main purpose of the present invention is to provide a high-adhesion silicon-containing adhesive and a preparation method thereof. The silicone resin adhesive has bonding strength, and at the same time has good flexibility, anti-aging yellowing ability, light transmittance, transmittance and low refractive index, and is more suitable for the preparation of film materials.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0008] On one hand, the present invention provides a high-adhesion silicon-containing adhesive, comprising a modified inorganic silicon adhesive and an organic silicon adhesive in a mass ratio of 1:(0.8-1.5); the modified inorganic silicon adhesive is composed of a hollow core layer and a shell layer; the outer layer of the shell layer is grafted with a structure shown in Formula I:

[0009]

[0010] wherein R1 is independently hydrogen, methyl, halogen, amine, epoxy, cyclohexene oxide, methacryl, acryl, hydroxyl, siloxy, isocyanate, nitrile, nitro, phenyl, C1-C40 alkyl, C2-C40 vinyl, C1-C40 alkoxy, C3-C40 cycloalkyl, C3-C40 heterocycloalkyl, C6-C40 aryl or C3-C40 heteroaryl;

[0011] R2 is independently hydrogen, methyl, halogen, amine, epoxy, cyclohexene oxide, methacryl, acryl, hydroxyl, siloxy, isocyanate, nitrile, nitro, phenyl, C1-C40 alkyl, C2-C40 vinyl, C1-C40 alkoxy, C3-C40 cycloalkyl, C3-C40 heterocycloalkyl, C6-C40 aryl or C3-C40 heteroaryl, including one methyl, vinylmethyl, styrene or perfluorovinylmethyl;

[0012] R3 is independently hydrogen, methyl, halogen, amine, epoxy, cyclohexene oxide, methacryl, propenyl, hydroxyl, siloxy, isocyanate, nitrile, nitro, phenyl, C1-C40 alkyl, C2-C40 vinyl, C1-C40 alkoxy, C3-C40 cycloalkyl, C3-C40 heterocycloalkyl, C6-C40 aryl or C3-C40 heteroaryl, which must contain one propenyl or methacryl;

[0013] x, y, and z are each independently an integer between 1 and 100; p is an integer between 1 and 200; is the grafting site with the shell;

[0014] The structure of structural unit A is as follows

[0015] in A is a chemical bond connection site; structural unit B is a cross-linker residue.

[0016] Preferably, x, y, and z are each independently an integer between 30 and 50; and p is an integer between 10 and 50.

[0017] Silicone adhesives are used in many fields, but with the development of electronic devices, some electronic devices are not limited to flat shapes. The emergence of some folding devices has put forward more stringent requirements on display screens. Adhesives, as an indispensable bonding material, also need to be improved. Traditional adhesives are very easy to crack after bending, affecting their use. At the same time, some adhesives are too hard after use and are not suitable for some film materials with special shapes. However, the current silicone adhesives cannot meet the requirements of excellent anti-aging and heat resistance while having good toughness and high light transmittance.

[0018] The present application prepares a self-made silicone resin adhesive which not only has good bonding force, but also has the characteristics of anti-aging performance, heat resistance, flexibility and low refractive index. The reasons may be that, on the one hand, the silicone resin adhesive of the present application has a core-shell structure, and the light transmittance and transmittance of the adhesive can be improved by complementary and synergistic means of a variety of different elements; on the other hand, the outermost layer of the silicone resin adhesive of the present application has a hindered phenol structure, which improves the anti-aging and yellowing performance of the adhesive; on the other hand, the present application cross-links the silicone resin adhesive through a cross-linking agent, thereby increasing its molecular weight and viscosity, and the phenyl groups therein can form π-π stacking, which improves the heat resistance of the adhesive. In addition, the adhesive contains a large number of unsaturated double bonds, which improves the impact strength of the adhesive.

[0019] In some embodiments, the structure of the organosilicon adhesive is as shown in Formula II:

[0020]

[0021] In some embodiments, the core layer and the shell layer of the silicone resin adhesive are independently any one of oxides of zirconium, tin, titanium and silicon, and the core layer and the shell layer are not the same oxide.

[0022] Another aspect of the present invention provides a method for preparing a high-adhesion silicon-containing adhesive, which comprises the following steps in parts by weight:

[0023] S1. Prepare a suspension of product A and product B after hydrolysis and polycondensation of any two of tin tetrachloride, zirconium tetrachloride, ethyl orthosilicate and tetrabutyl titanate with water, heat to reflux, continue stirring for 2 to 3 hours, centrifuge after the reaction, wash with ethanol and dry, and calcine at 500 to 600° C. to obtain an inorganic silicon adhesive.

[0024] S2, 80-90 parts of an organosiloxane containing an R1 group, 80-90 parts of an organosiloxane containing an R2 group and 80-90 parts of an organosiloxane containing an R3 group are mixed, 170-180 parts of toluene, 45-50 parts of deionized water and 2-4 parts of concentrated sulfuric acid are added, the temperature is raised to 70-80° C. and stirred at a constant temperature for 1-2 hours, after the reaction is completed, 35-45 parts of a compound containing a structural unit A and 160-180 parts of heptane are added, the temperature is raised to 40-50° C. and the reaction is continued for 12-14 hours, after the reaction is completed, the mixture is cooled to room temperature to obtain a polysiloxane copolymer precursor;

[0025] S3, in an inert protective gas atmosphere, 60-70 parts of tetraethyl orthosilicate, 180-220 parts of the inorganic silicone adhesive in step S1, 80-90 parts of the polysiloxane copolymer precursor and the crosslinking agent in step S2 are mixed, triethylamine is added, the temperature is raised to 70-80° C., and the mixture is stirred at a constant temperature for 1-3 hours. After the reaction is completed, a modified inorganic silicone adhesive is obtained;

[0026] S4, mixing and stirring the organic silicon adhesive and the inorganic silicon adhesive in step S3 to obtain a silicon-containing adhesive with high adhesion.

[0027] In some embodiments, in step S3, the cross-linking agent has any one of the following structures:

[0028] (1)

[0029] (2) wherein n is an integer of 0 to 8, and R4 is any one of -COOH, -OH, -SH or -NCO.

[0030] The present application can increase the molecular weight of the adhesive and improve the bonding strength by adding a cross-linking agent, and at the same time, the phenyl groups in the cross-linking agent can form a π-π stacking structure, thereby improving the high temperature resistance of the adhesive.

[0031] In some embodiments, in step S1, the mass ratio of any two of the compounds selected from tin tetrachloride, zirconium tetrachloride, ethyl orthosilicate and tetrabutyl titanate is 1:(2-4).

[0032] In some embodiments, in step S3, the amount of the cross-linking agent added is 0.1-0.3% of the total mass of tetraethyl orthosilicate and polysiloxane copolymer precursor.

[0033] In some embodiments, the preparation method of the compound containing structural unit A comprises the following steps: mixing 3-amino-1-propanol and 2,6-di-tert-butyl-4-chlorophenol, adding them to N,N-dimethylformamide, adding an acid binding agent, heating to 35-45° C. and stirring at a constant temperature for 12-14 hours, filtering after the reaction is completed, and obtaining a compound containing structural unit A.

[0034] The present application uses a compound containing structural unit A to end-cap the silicone resin adhesive, thereby improving the anti-aging and yellowing performance of the silicone adhesive. The reason may be that the structural unit A contains a hindered phenol structure, which can improve the anti-aging and yellowing performance of the adhesive.

[0035] In some embodiments, the molar ratio of the 3-amino-1-propanol to the 2,6-di-tert-butyl-4-chlorophenol is 1:(1-1.3).

[0036] In some embodiments, the acid binding agent is any one of sodium carbonate, potassium carbonate, sodium bicarbonate and potassium bicarbonate.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] (1) The adhesive of the present invention is prepared by compounding a modified inorganic silicone adhesive and an organic silicone adhesive. On the one hand, the modified inorganic silicone adhesive has a hollow core-shell structure, and the light transmittance and transmittance of the adhesive can be improved by the complementary and synergistic combination of a variety of different elements; on the other hand, the outermost layer of the modified inorganic silicone adhesive has a hindered phenol structure, which improves the adhesive's anti-aging and yellowing properties; on the other hand, the adhesive is cross-linked by a cross-linking agent, which increases its molecular weight and viscosity, and the phenyl groups therein can form π-π stacking, thereby improving the heat resistance of the adhesive. In addition, the organic silicone adhesive contains a large number of unsaturated double bonds, which improves the impact strength of the adhesive.

[0039] (2) The compound containing structural unit A of the present invention can end-cap the silicone resin adhesive and improve the anti-aging and yellowing performance of the silicone adhesive. The reason may be that the structural unit A contains a hindered phenol structure, which can improve the anti-aging and yellowing performance of the adhesive.

[0040] (3) The present invention can increase the molecular weight of the adhesive and improve the bonding strength by adding a cross-linking agent. At the same time, the phenyl groups in the cross-linking agent can form a π-π stacking structure, thereby improving the high temperature resistance of the adhesive. At the same time, by using a specific ratio of cross-linking agent, tetraethyl orthosilicate and polysiloxane, it can prevent the initial molecular weight from being too high, which will cause the fluidity of the adhesive to decrease and be unfavorable for leveling. DETAILED DESCRIPTION

[0041] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] Preparation Example 1

[0043] The preparation method of a compound containing structural unit A comprises the following steps: mixing 0.3 mol of 3-amino-1-propanol and 0.36 mol of 2,6-di-tert-butyl-4-chlorophenol, adding into 300 mL of N,N-dimethylformamide, adding 0.42 mol of sodium bicarbonate, heating to 40° C. and stirring at constant temperature for 13 hours, filtering after the reaction is completed, and obtaining a compound containing structural unit A.

[0044] Preparation Example 2

[0045] The preparation method of the compound containing structural unit A is the same as that of Preparation Example 1, except that 2,6-di-tert-butyl-4-chlorophenol is not added.

[0046] Example 1

[0047] A high-adhesive silicon-containing adhesive comprises a modified inorganic silicon adhesive and an organic silicon adhesive in a mass ratio of 1:1.3; the modified inorganic silicon adhesive comprises a hollow core layer and a shell layer; the outer layer of the shell layer is grafted with a structure shown in Formula I:

[0048] Wherein, R1 is methyl, R2 is methyl and hydrogen, R3 is propenyl and hydroxyl; x is 40, y is 40, z is 40; p is 30; is the grafting site with the shell layer; the structure of structural unit A is as follows

[0049] in A is a chemical bond connection site; structural unit B is a cross-linker residue.

[0050] The preparation method of the high-adhesion silicon-containing adhesive comprises the following steps, measured by weight:

[0051] S1. Mix 100 parts of tetraethyl orthosilicate, 2L of deionized water and 70mL of 2mol / L sodium hydroxide solution, and perform hydrolysis and polycondensation at room temperature for 3h. Centrifuge to obtain product A. Prepare material A by mixing 300 parts of tetrabutyl titanate and 900 parts of ethanol. Prepare material B by mixing 900 parts of ethanol, 90 parts of deionized water and 72 parts of glacial acetic acid. Add material B to material A and stir at room temperature for 2h. Centrifuge to obtain product B. Mix product A and product B with 2.5L of deionized water to form a suspension. Heat to reflux state. Continue stirring for 2.5h. Centrifuge after the reaction. Wash with ethanol and dry. Calcined at 550°C to obtain an inorganic silicon adhesive.

[0052] S2, 85 parts of dimethyldimethoxysilane, 85 parts of methyldiethoxysilane and 85 parts of allyltriethoxysilane were mixed, 175 parts of toluene, 47 parts of deionized water and 3 parts of 98wt% concentrated sulfuric acid were added, the temperature was raised to 75°C and stirred at constant temperature for 1.5h, after the reaction was completed, 40 parts of the compound containing structural unit A and 170 parts of heptane were added, the temperature was raised to 45°C and the reaction was continued for 13h, and after the reaction was completed, the reaction was cooled to room temperature to obtain a polysiloxane copolymer precursor;

[0053] S3, in a N2 gas atmosphere, 7 parts of tetraethyl orthosilicate, 200 parts of the inorganic silicone adhesive in step S1, 85 parts of the polysiloxane copolymer precursor in step S2 and 0.2 parts of terephthalic acid methanol were mixed, 20 parts of triethylamine were added, the temperature was raised to 75°C, and the mixture was stirred at a constant temperature for 2 hours. After the reaction was completed, a modified inorganic silicone adhesive was obtained;

[0054] S4, mixing and stirring the organic silicon adhesive and the inorganic silicon adhesive in step S3 to obtain a silicon-containing adhesive with high adhesion.

[0055] Wherein, the compound containing structural unit A is prepared by Preparation Example 1; the structure of the organic silicon adhesive is shown in Formula II:

[0056]

[0057] Example 2

[0058] A high-adhesive silicon-containing adhesive comprises a modified inorganic silicon adhesive and an organic silicon adhesive in a mass ratio of 1:0.8; the modified inorganic silicon adhesive comprises a hollow core layer and a shell layer; the outer layer of the shell layer is grafted with a structure shown in Formula I:

[0059] Wherein, R1 is methyl, R2 is methyl and hydrogen, R3 is propenyl and hydroxyl; x is 40, y is 40, z is 40; p is 30; is the grafting site with the shell layer; the structure of structural unit A is as follows

[0060] in A is a chemical bond connection site; structural unit B is a cross-linker residue.

[0061] The preparation method of the high-adhesion silicon-containing adhesive comprises the following steps, measured by weight:

[0062] S1. Mix 100 parts of tetraethyl orthosilicate, 2L of deionized water and 70mL of 2mol / L sodium hydroxide solution, hydrolyze and polycondense at room temperature for 3h, and obtain product A after centrifugation. Prepare material A by mixing 200 parts of tetrabutyl titanate and 600 parts of ethanol, prepare material B by mixing 600 parts of ethanol, 60 parts of deionized water and 16 parts of glacial acetic acid, add material B to material A and stir at room temperature for 2h, and obtain product B after centrifugation. Mix product A and product B with 1L of deionized water to form a suspension, heat to reflux state, continue stirring for 2h, centrifuge after the reaction, wash with ethanol and dry, and calcine at 500°C to obtain an inorganic silicon adhesive;

[0063] S2, 80 parts of dimethyldimethoxysilane, 80 parts of methyldiethoxysilane and 80 parts of allyltriethoxysilane were mixed, 170 parts of toluene, 45 parts of deionized water and 2 parts of 98wt% concentrated sulfuric acid were added, the temperature was raised to 70°C and stirred at constant temperature for 2h, after the reaction was completed, 35 parts of the compound containing structural unit A and 160 parts of heptane were added, the temperature was raised to 40°C and the reaction was continued for 14h, and after the reaction was completed, the reaction was cooled to room temperature to obtain a polysiloxane copolymer precursor;

[0064] S3, in a N2 gas atmosphere, 60 parts of tetraethyl orthosilicate, 180 parts of the inorganic silicone adhesive in step S1, 80 parts of the polysiloxane copolymer precursor in step S2 and 0.14 parts of terephthalic acid methanol were mixed, 20 parts of triethylamine were added, the temperature was raised to 70°C, and the mixture was stirred at a constant temperature for 3 hours. After the reaction was completed, a modified inorganic silicone adhesive was obtained;

[0065] S4, mixing and stirring the organic silicon adhesive and the inorganic silicon adhesive in step S3 to obtain a silicon-containing adhesive with high adhesion.

[0066] Wherein, the compound containing structural unit A is prepared by Preparation Example 1; the structure of the organic silicon adhesive is shown in Formula II:

[0067]

[0068] Example 3

[0069] A high-adhesive silicon-containing adhesive comprises a modified inorganic silicon adhesive and an organic silicon adhesive in a mass ratio of 1:1.5; the modified inorganic silicon adhesive comprises a hollow core layer and a shell layer; the outer layer of the shell layer is grafted with a structure shown in Formula I:

[0070] Wherein, R1 is methyl, R2 is methyl and hydrogen, R3 is propenyl and hydroxyl; x is 40, y is 40, z is 40; p is 30; is the grafting site with the shell layer; the structure of structural unit A is as follows

[0071] in A is a chemical bond connection site; structural unit B is a cross-linker residue.

[0072] The preparation method of the high-adhesion silicon-containing adhesive comprises the following steps, measured by weight:

[0073] S1. Mix 100 parts of tetraethyl orthosilicate, 2L of deionized water and 70mL of 2mol / L sodium hydroxide solution, hydrolyze and polycondense at room temperature for 3h, and obtain product A after centrifugation. Prepare material A by mixing 400 parts of tetrabutyl titanate and 1200 parts of ethanol, prepare material B by mixing 1200 parts of ethanol, 120 parts of deionized water and 32 parts of glacial acetic acid, add material B to material A and stir at room temperature for 2h, and obtain product B after centrifugation. Mix product A and product B with 4.5L of deionized water to form a suspension, heat to reflux state, continue stirring for 3h, centrifuge after the reaction, wash with ethanol and dry, and calcine at 600°C to obtain an inorganic silicon adhesive;

[0074] S2, 90 parts of dimethyldimethoxysilane, 90 parts of methyldiethoxysilane and 90 parts of allyltriethoxysilane were mixed, 180 parts of toluene, 50 parts of deionized water and 4 parts of 98wt% concentrated sulfuric acid were added, the temperature was raised to 80°C and stirred at constant temperature for 1h, after the reaction was completed, 45 parts of the compound containing structural unit A and 180 parts of heptane were added, the temperature was raised to 50°C and the reaction was continued for 12h, and after the reaction was completed, the reaction was cooled to room temperature to obtain a polysiloxane copolymer precursor;

[0075] S3, in a N2 gas atmosphere, 70 parts of tetraethyl orthosilicate, 220 parts of the inorganic silicone adhesive in step S1, 90 parts of the polysiloxane copolymer precursor in step S2 and 0.48 parts of terephthalic acid methanol were mixed, 20 parts of triethylamine were added, the temperature was raised to 80°C, and the mixture was stirred at a constant temperature for 1 hour. After the reaction was completed, a modified inorganic silicone adhesive was obtained;

[0076] S4, mixing and stirring the organic silicon adhesive and the inorganic silicon adhesive in step S3 to obtain a silicon-containing adhesive with high adhesion.

[0077] Wherein, the compound containing structural unit A is prepared by Preparation Example 1; the structure of the organic silicon adhesive is shown in Formula II:

[0078]

[0079] Example 4

[0080] A high-adhesion silicon-containing adhesive and a preparation method thereof. The specific implementation manner is the same as that of Example 1, except that the compound containing structural unit A is prepared by Preparation Example 2.

[0081] Comparative Example 1

[0082] A high-adhesion silicon-containing adhesive and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that tetrabutyl titanate is not added.

[0083] Comparative Example 2

[0084] A high-adhesion silicon-containing adhesive and a preparation method thereof. The specific implementation manner is the same as that of Example 1, except that an equal mass portion of 2,6-di-tert-butyl-4-chlorophenol is used to replace the compound containing structural unit A.

[0085] Comparative Example 3

[0086] A high-adhesion silicon-containing adhesive and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that an equal mass portion of 4-hexylheptanediol is used instead of terephthalic acid.

[0087] Performance Testing:

[0088] (1) Anti-ultraviolet performance: Take a high-transmittance glass sheet, apply a 0.5 mm thick silicon-containing adhesive on its surface to obtain an adhesive layer, and let it stand for curing at room temperature for 2 h. Place the coating facing the light side in a UV aging box, use a 1 kW lamp tube, and 50 cm away for continuous irradiation for 100 h. Calculate the yellowing index of the adhesive layer according to GB / T7975-2005 standard;

[0089] (2) Peel strength: A 0.2 mm thick silicon-containing adhesive was applied to the surface of a marble sheet to obtain an adhesive layer, which was cured at 50°C for 40 min and then left to stand for one day. A peel test was performed according to GB / T2792-2014. Elongation test: The adhesive was applied to form a 2 mm thin film, cured for 14 days, cut into dumbbell shapes, and tested using a tensile testing machine at a rate of 50 mm / min. The greater the elongation, the better the toughness.

[0090] (3) Temperature resistance: The film prepared in method (2) was placed in a 300°C environment for 3 days and the elongation was tested again;

[0091] (4) Transmittance test: measured by spectrophotometer UV3100, wavelength range 400~700nm;

[0092] (5) Light transmittance test: measured using a photoelectric haze meter model NDH2000.

[0093] The adhesives of the embodiments and comparative examples were tested according to the above test method. The results are shown in Table 1.

[0094] Table 1

[0095]

[0096] According to the above results, it is found that the silicone resin adhesives of Examples 1 to 3 have good anti-yellowing ability and bonding performance, and have good toughness, high temperature resistance, light transmittance and transmittance; in Example 4, due to the lack of addition of 2,6-di-tert-butyl-4-chlorophenol, the anti-yellowing performance of the adhesive is reduced, and the elongation at high temperature is reduced due to the weakening of its anti-aging performance; in Comparative Example 1, due to the lack of addition of tetrabutyl titanate, the light transmittance and transmittance of the adhesive are reduced; in Comparative Example 2, due to the use of equal parts of 2,6-di-tert-butyl-4-chlorophenol instead of the compound containing structural unit A, due to the poor compatibility of 2,6-di-tert-butyl-4-chlorophenol with the adhesive, precipitation occurs during the test, and the anti-yellowing performance of the adhesive is reduced; in Comparative Example 3, due to the use of equal parts of 4-heterobutylene glycol instead of terephthalic acid, the temperature resistance of the adhesive is reduced.

[0097] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. A high-adhesion silicon-containing adhesive, characterized in that: The invention comprises a modified inorganic silicon adhesive and an organic silicon adhesive in a mass ratio of 1:(0.8-1.5); the modified inorganic silicon adhesive is composed of a hollow core layer and a shell layer; the outer layer of the shell layer is grafted with a structure shown in Formula I: wherein R1 is independently hydrogen, methyl, halogen, amine, epoxy, cyclohexene oxide, methacryl, acryl, hydroxyl, siloxy, isocyanate, nitrile, nitro, phenyl, C1-C40 alkyl, C2-C40 vinyl, C1-C40 alkoxy, C3-C40 cycloalkyl, C3-C40 heterocycloalkyl, C6-C40 aryl or C3-C40 heteroaryl; R2 is independently hydrogen, methyl, halogen, amine, epoxy, cyclohexene oxide, methacryl, acryl, hydroxyl, siloxy, isocyanate, nitrile, nitro, phenyl, C1-C40 alkyl, C2-C40 vinyl, C1-C40 alkoxy, C3-C40 cycloalkyl, C3-C40 heterocycloalkyl, C6-C40 aryl or C3-C40 heteroaryl, including one methyl, vinylmethyl, styrene or perfluorovinylmethyl; R3 is independently hydrogen, methyl, halogen, amine, epoxy, cyclohexene oxide, methacryl, propenyl, hydroxyl, siloxy, isocyanate, nitrile, nitro, phenyl, C1-C40 alkyl, C2-C40 vinyl, C1-C40 alkoxy, C3-C40 cycloalkyl, C3-C40 heterocycloalkyl, C6-C40 aryl or C3-C40 heteroaryl, which must contain one propenyl or methacryl; x, y, and z are each independently an integer between 1 and 100; p is an integer between 1 and 200; is the grafting site with the shell; The structure of structural unit A is as follows in A is a chemical bond connection site; structural unit B is a cross-linker residue.

2. The high-adhesion silicon-containing adhesive according to claim 1, characterized in that: The structure of the organic silicon adhesive is shown in Formula II:

3. The high-adhesion silicon-containing adhesive according to claim 1, characterized in that: The core layer and the shell layer of the organic silicone resin adhesive are independently any one of the oxides of zirconium, tin, titanium and silicon, and the core layer and the shell layer are not the same oxide.

4. A method for preparing a high-adhesion silicon-containing adhesive according to any one of claims 1 to 3, characterized in that: By weight, the method comprises the following steps: S1. Prepare a suspension of product A and product B after hydrolysis and polycondensation of any two of tin tetrachloride, zirconium tetrachloride, ethyl orthosilicate and tetrabutyl titanate with water, heat to reflux, continue stirring for 2 to 3 hours, centrifuge after the reaction, wash with ethanol and dry, and calcine at 500 to 600° C. to obtain an inorganic silicon adhesive; S2, 80-90 parts of an organosiloxane containing an R1 group, 80-90 parts of an organosiloxane containing an R2 group and 80-90 parts of an organosiloxane containing an R3 group are mixed, 170-180 parts of toluene, 45-50 parts of deionized water and 2-4 parts of concentrated sulfuric acid are added, the temperature is raised to 70-80° C. and stirred at a constant temperature for 1-2 hours, after the reaction is completed, 35-45 parts of a compound containing a structural unit A and 160-180 parts of heptane are added, the temperature is raised to 40-50° C. and the reaction is continued for 12-14 hours, after the reaction is completed, the mixture is cooled to room temperature to obtain a polysiloxane copolymer precursor; S3, in an inert protective gas atmosphere, 60-70 parts of tetraethyl orthosilicate, 180-220 parts of the inorganic silicone adhesive in step S1, 80-90 parts of the polysiloxane copolymer precursor and the crosslinking agent in step S2 are mixed, triethylamine is added, the temperature is raised to 70-80° C., and the mixture is stirred at a constant temperature for 1-3 hours. After the reaction is completed, a modified inorganic silicone adhesive is obtained; S4, mixing and stirring the organic silicon adhesive and the inorganic silicon adhesive in step S3 to obtain a silicon-containing adhesive with high adhesion.

5. The method for preparing a high-adhesion silicon-containing adhesive according to claim 4, characterized in that: In step S3, the cross-linking agent has any one of the following structures: (1) (2) wherein n is an integer of 0 to 8, and R4 is any one of -COOH, -OH, -SH or -NCO.

6. The method for preparing a high-adhesion silicon-containing adhesive according to claim 4, characterized in that: In step S1, the mass ratio of any two of the tin tetrachloride, zirconium tetrachloride, ethyl orthosilicate and tetrabutyl titanate is 1:(2-4).

7. The method for preparing a high-adhesion silicon-containing adhesive according to claim 4, characterized in that: In step S3, the added amount of the cross-linking agent is 0.1-0.3% of the total mass of tetraethyl orthosilicate and polysiloxane copolymer precursor.

8. The method for preparing a high-adhesion silicon-containing adhesive according to claim 4, characterized in that: The preparation method of the compound containing structural unit A comprises the following steps: mixing 3-amino-1-propanol and 2,6-di-tert-butyl-4-chlorophenol, adding the mixture into N,N-dimethylformamide, adding an acid binding agent, heating the mixture to 35-45° C., stirring the mixture at a constant temperature for 12-14 hours, filtering the mixture after the reaction is completed, and obtaining the compound containing structural unit A.

9. The method for preparing a high-adhesion silicon-containing adhesive according to claim 8, characterized in that: The molar ratio of the 3-amino-1-propanol to the 2,6-di-tert-butyl-4-chlorophenol is 1:(1-1.3).

10. The method for preparing a high-adhesion silicon-containing adhesive according to claim 8, characterized in that: The acid binding agent is any one of sodium carbonate, potassium carbonate, sodium bicarbonate and potassium bicarbonate.

Citation Information

Patent Citations

  • Thermally conductive silicone adhesive

    CN110819299B

  • Silicone adhesive composition and use thereof

    CN113286863A